Communicative Constructions and the Refiguration of Spaces Theoretical Approaches and Empirical Studies - Christmann, Gabriela B.; Knoblauch, Hubert; Löw, Martina (Taylor & Francis, 2022)
The Open Access version of this book, available at www.taylorfrancis.com , has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license Through a variety of empirical studies, this volume offers fresh insights into the manner in which different forms of communicative action transform urban space. With attention to the methodological questions that arise from the attempt to study such changes empirically, it offers new theoretical foundations for understanding the social construction and reconstruction of spaces through communicative action. Seeing communicative action as the basic element in the social construction of reality and conceptualizing communication not only in terms of the use of language and texts, but as involving any kind of objectification, such as technologies, bodies and non-verbal signs, it considers the roles of both direct and mediatized (or digitized) communication. An examination of the conceptualization of the communicative (re-)construction of spaces and the means by which this change might be empirically investigated, this book demonstrates the fruitfulness of the notion of refiguration as a means by which to understand the transformation of contemporary societies. As such, it will appeal to sociologists, social theorists, and geographers with interests in social construction and urban space.